REFORMULASI KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PEJUDIAN ONLINE - Ginta Amelia Cahya; Ali Masyhar; Cahya Wulandari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of information technology has given rise to new forms of crime, one of which is online gambling, characterized by its cross-border nature, anonymity, and digital system-based operations. However, the criminal punishment of such offenses in Indonesia still relies on Article 303 of the Indonesian Criminal Code (KUHP), which was originally designed to regulate conventional gambling. This condition creates juridical problems because the application of outdated legal norms to online gambling is often carried out through analogical interpretation, which potentially contradicts the principle of legality (nullum crimen sine lege). This study aims to analyze the current criminal punishment framework for online gambling offenses and examine the urgency of reformulating criminal law policy regarding online gambling in Indonesia. The research employs a normative juridical method using statutory, conceptual, and case study approaches to relevant court decisions. The legal materials consist of primary legal sources in the form of legislation and secondary legal sources such as legal literature, journals, and expert doctrines. The analysis is conducted qualitatively and descriptively by examining the compatibility of existing legal norms with the development of digital crimes. The results of the study indicate that Article 303 of the Criminal Code is no longer capable of addressing the complexity of online gambling, particularly in terms of offense formulation, legal subjects, and operational mechanisms of digital crime. The existing criminal sanctions are also considered disproportionate to the socio-economic impacts caused, such as money laundering, public financial losses, and increasing derivative crimes. Therefore, the reformulation of criminal law policy has become an urgent necessity through the establishment of specific legal norms explicitly regulating the definition of online gambling, forms of conduct, criminal liability, and proportional sanctions. Thus, the national criminal law system can become more responsive, effective, and capable of providing legal certainty in addressing the development of digital crime. Keywords: Criminal Law Reformulation, Online Gambling, Criminal Policy, Principle Of Legality, Digital Crime.